Quercetin alleviates cyclophosphamide-induced premature ovarian insufficiency in mice by reducing mitochondrial oxidative stress and pyroptosis in granulosa cells - Yun Chen; Ying Zhao; Chenyun Miao; Liuqing Yang; Ruye Wang; Bixia Chen; Qin Zhang (Journal of Ovarian Research, 2022)
Abstract Background Exposure to cyclophosphamide (CTX) induces premature ovarian insufficiency (POI). Quercetin is a natural flavonoid that exhibits anti-inflammatory and antioxidant properties, and its antioxidant activity is correlated with POI. However, the mechanism underlying its protective role in CTX-induced ovarian dysfunction is unclear. This study aimed to explore whether quercetin can protect ovarian reserves by activating mitochondrial biogenesis and inhibiting pyroptosis. Methods Thirty-six female C57BL/6 mice were randomly subdivided into six groups. Except for the control group, all groups were injected with 90 mg/kg CTX to establish a POI model and further treated with coenzyme 10 or various doses of quercetin. The mice were sacrificed 48 h after 10 IU pregnant mare serum gonadotropin was injected four weeks after treatments. We used enzyme-linked immunosorbent assays to detect serum hormone expression and light and transmission electron microscopy to assess ovarian tissue morphology and mitochondria. Additionally, we tested oxidant and antioxidant levels in ovarian tissues and mitochondrial function in granulosa cells (GCs). The expression of mitochondrial biogenesis and pyroptosis-related proteins and mRNA was analyzed using western blotting and RT-qPCR. Results Quercetin elevated serum anti-Müllerian hormone, estradiol, and progesterone levels, decreased serum follicle-stimulating hormone and luteinizing hormone levels, and alleviated ovarian pathology. It reduced the mitochondrial DNA content and mitochondrial membrane potential. Furthermore, it upregulated ATP levels and the mRNA and protein expression of peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC1α), mitochondrial transcription factor A, and superoxide dismutase 2. In addition, it suppressed NOD-like receptor pyrin domain containing 3, caspase-1, interleukin-1β, and gasdermin D levels in the GCs of POI mice. Conclusions Quercetin protected the ovarian reserve from CTX-induced ovarian damage by reversing mitochondrial dysfunction and activating mitochondrial biogenesis via the PGC1-α pathway. Moreover, quercetin may improve ovarian functions by downregulating pyroptosis in the CTX-induced POI model. Thus, quercetin can be considered a potential agent for treating POI.